2021
DOI: 10.1111/ijcp.14593
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of aromatherapy inhalation on anxiety and haemodynamic variables for patients with cardiovascular disease: A systematic review and meta‐analysis

Abstract: Background: Anxiety can negatively affect patients' prognosis in cardiovascular disease. Aromatherapy helps reduce anxiety level in chronic diseases. However, the effectiveness of aromatherapy on anxiety and haemodynamic variables remains uncertain.Objective: To evaluate the evidence for the effectiveness of aromatherapy on anxiety and haemodynamic variables in patients with cardiovascular disease.Design: A systematic review and meta-analysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 56 publications
(348 reference statements)
0
5
0
Order By: Relevance
“…[11,12]. In addition to several studies, it has been shown to have a positive and therapeutic e ect of aromatherapy in reducing anxiety in patients with cardiovascular disease [13]. However, a comprehensive review study about the potential e ects of aromatherapy in various cardiovascular diseases such as ischemia, open heart surgery, and angiography has not yet been made, so the purpose of this study was a comprehensive review of studies on the e ect of aromatherapy with plant essential oils on the improvement of some conditions, for example, anxiety, stress, sleep quality, fatigue, and pain in people with cardiovascular disease.…”
Section: Introductionmentioning
confidence: 99%
“…[11,12]. In addition to several studies, it has been shown to have a positive and therapeutic e ect of aromatherapy in reducing anxiety in patients with cardiovascular disease [13]. However, a comprehensive review study about the potential e ects of aromatherapy in various cardiovascular diseases such as ischemia, open heart surgery, and angiography has not yet been made, so the purpose of this study was a comprehensive review of studies on the e ect of aromatherapy with plant essential oils on the improvement of some conditions, for example, anxiety, stress, sleep quality, fatigue, and pain in people with cardiovascular disease.…”
Section: Introductionmentioning
confidence: 99%
“…For example, they induce an antiplatelet effect, help lower blood pressure, reduce lipids and glucose, and attenuate diabetes symptoms in patients as a complementary treatment (37). Moreover, when they induce relaxation in patients and alleviate the stress and anxiety of the patients, hemodynamic parameters are indirectly adjusted due to the patient's mental disorder (38). Aromatic plant essential oils are mainly composed of citronellol, geraniol, nerol, kaempferol, 2-phenylethanol, nonadecane, and heneicosane (39).…”
Section: Main Mechanisms Of Actionmentioning
confidence: 99%
“…Aromatherapy, which involves the use of volatile plant oils through inhalation or other methods, has been explored as a potential treatment for various conditions, including PONV [ 22 ], anxiety [ 23 ], insomnia [ 24 ], dysmenorrhea [ 25 ], and dementia [ 26 ]. Various studies have explored the use of essence from ginger [ 27 28 29 ], peppermint essential oil [ 30 31 ], as well as lavender and clary sage oil [ 32 ] for the prevention of PONV.…”
Section: Introductionmentioning
confidence: 99%